2009
DOI: 10.1111/j.1467-9280.2009.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wick in the Candle of Learning

Abstract: Curiosity has been described as the "wick in the candle of learning" but its underlying mechanisms are not well-understood. We scanned subjects with fMRI while they read trivia questions. The level of curiosity when reading questions is correlated with activity in caudate regions previously suggested to be involved in anticipated reward or encoding prediction error. This finding led to a behavioral study showing that subjects spend more scarce resources (either limited tokens, or waiting time) to find out answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
400
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 652 publications
(458 citation statements)
references
References 40 publications
53
400
4
1
Order By: Relevance
“…Curiosity on its own has been demonstrated to mimic extrinsic reward anticipation and novelty. For example, Kang et al (2009) found that curiosity is associated with higher arousal (increased pupil dilation) and elevated striatal and prefrontal BOLD activity during anticipation of the outcome (in this case, the answer to an interesting quiz question).…”
Section: Individual Differences In Reward Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Curiosity on its own has been demonstrated to mimic extrinsic reward anticipation and novelty. For example, Kang et al (2009) found that curiosity is associated with higher arousal (increased pupil dilation) and elevated striatal and prefrontal BOLD activity during anticipation of the outcome (in this case, the answer to an interesting quiz question).…”
Section: Individual Differences In Reward Sensitivitymentioning
confidence: 99%
“…Therefore, presentation of a reward (or a novel stimulus) may affect events occurring several seconds to minutes afterward, during the time when the evoked dopaminergic input from the VTA reaches the hippocampus. Gruber et al, 2014, (using a paradigm similar to Kang et al, 2009) found that a state of high curiosity (i.e., a state of intrinsic reward motivation) was associated with NAc and VTA activation and led to better free recall memory for trivia questions the participants were curious about, 1h after the encoding. Furthermore, this experiment directly tested the penumbra hypothesis by showing participants faces during the answer anticipation period.…”
Section: Incidental Learning During State Of Reward Motivationmentioning
confidence: 99%
“…This role of self-efficacy on state curiosity in this knowledge strata was found to be as strong as the role of trait curiosity [18]. [20] found that the relationship between curiosity and self-efficacy may actually be an inverted u-shape suggesting that low curiosity levels may be due to either very low or very high self-efficacy. This points to further need to understand the self-efficacy of a learner in order to be able to provide appropriate intervention to address their curiosity levels.…”
Section: Opportunities In Monitoring Self-efficacy Curiosity and Rementioning
confidence: 88%
“…The authors found that in cases where participants indicated not knowing the answer or that it was on the tip of their tongue, the reported level of confidence in the ability to identify the correct answer if given multiple options predicted the level of curiosity for the correct answer. Curiosity itself is an important state in learning as it directly affects information seeking behaviour [19] [20]. For example, [18] found higher levels of curiosity about the correct trivia answers to be significantly positively correlated with efforts made to retrieve these answers.…”
Section: The Influence Of Self-efficacy Curiosity and Reflectivity mentioning
confidence: 98%
See 1 more Smart Citation